High temperature oxidation behavior of C-Mn steels containing As/Cu-As - XIN Wen-bin; SONG Bo; HU Chun-lin; SONG Ming-ming; SUN Gui-lin (工程科学学报)
The high temperature oxidation characteristics of C-Mn steels containing As or Cu + As were investigated by thermo-gravimetry, scanning electron microscopy, and electron probe micro-analysis. It is shown that the oxidation kinetic curves at 1050℃ obey a linear law in the first 500 s and subsequently change to a parabolic law. The parabolic oxidation rates of the As and Cu-As steels are higher than that of the C-Mn steel. Due to separation of the scale from the matrix, the mass increment of the steels at 1150℃ is smaller than that at 1050℃. Cu and As in the steels could promote solid Fe2SiO4 layer growth. A significant internal oxidation particle layer is observed in the As steel because of As enrichment at the scale/steel interface at 1050℃. The interface is found to be uneven when Cu and As are added to the C-Mn steel, and the number of internal oxides increases with increasing oxidation time and temperature. The oxidation enrichment degree of Cu and As at the scale/steel interface at 1050℃ is higher than that at 1150℃.